James I and his Era. Brief Analysis of a Major Political and Cultural Inheritance - Antoni Riera (Catalan Historical Review, 2008)
We have gathered here at Poblet, the solemn burial place of the royal houses of Aragon and Catalonia, to remember a birth, not a death, and to celebrate the first of several institutional events to commemorate the eight-hundredth anniversary of the birth of James I, one of the sovereigns who are interred here.